Introducing Infinity: A Graphic Guide - Brian Clegg (Icon Books, 2012)
A brand new graphic guide from Brian Clegg, author of the best-selling Inflight Science, Introducing Infinity will teach you all you need to know about this big idea, from mathematicians driven mad by transfinite numbers to the ancient Greeks who drowned the man that discovered an endless number.